ANALYSIS OF THE CURRENT SITUATION OF THE PAKHTAKOR PUMPING STATION UNDER THE AMU-KASHKADARYA IRRIGATION SYSTEM DEPARTMENT OF THE MINISTRY OF WATER RESOURCES AND DEPARTMENT OF ENERGY - Tuychiyev Ahror Jovli o’g’li (Modern American Journals, 2025)
This article aims to study the hydraulic process, calculate and reduce the resistances in the channels of the pumping station of the pumping in station and pumping out station. In the conditions of water shortage and limited resources in the republic, in the process of deepening market economy reforms, the cultivation of agricultural products, improvement of their quality, application of advanced practices and new irrigation technologies, rational and productive use of land and water resources are of strategic importance. Taking into account the fact that it is the route, ways of saving water in the efficient use of water, in this case, saving the water that is not in the irrigation field, but the water that is before reaching the field or the raised water that should be given, the water of machine channels. It consists of scientifically based proposals and recommendations for the development of measures to improve the carrying capacity and to reduce the operating costs in the machine irrigation system. Repairing, designing, extending the service life of pumping station facilities and equipment, increasing their productivity, saving electricity, reducing water wastage, protecting the environment and preventing emergency situations, providing timely, high-quality service, automatic focused on effective technical and economic use of tools and equipment.
Keywords: Advance camera, aggregate, characteristic, hydrotechnical facility, a water channel, pump assembly, horizontal, cavitation, zadwijka, valve.